Penguatan Etika Bisnis dan Keadilan Pasar Berbasis Pemikiran Al-Syaibani dan Yahya Bin Umar pada Pelaku UMKM di Kecamatan Kademangan Kota Probolinggo - Diana Rizky Amalia; Fitri Dian Wilujeng; Adika Desi Setyani (LPPM STAI Muhammadiyah Probolinggo, 2026)
This community service activity aims to strengthen business ethics and market justice among Micro, Small, and Medium Enterprises (MSMEs) actors in Kademangan District, Probolinggo City, based on the thought of Al-Syaibani and Yahya bin Umar. This study employed a Participatory Action Research (PAR) approach. Participants consisted of 40 MSME actors selected by purposive sampling. The results showed that before the program, the average understanding of business ethics was 2.74 (Poor category), whereas after the training intervention it increased significantly to 4.21 (Very Good category), with an improvement percentage of 53.6%. In the aspect of market justice, the mean score rose from 2.61 to 4.18 (increase of 60.2%). These findings indicate that integration of Al-Syaibani's work ethics thinking and Yahya bin Umar's market supervision principles in community service activities is highly effective in improving the awareness and practice of business ethics and market justice among MSME actors. The program contributes to strengthening Islamic economic values at the grassroots level and can serve as a replicable model for similar community engagement programs